Dengue virus and antiplatelet autoantibodies synergistically induce haemorrhage through Nlrp3-inflammasome and FcүRIII - Lien, Te-Sheng; Sun, Der-Shan; Chang, Chia-Ming; Wu, Cheng-Yeu; Dai, Ming-Shen; Chan, Hao; Wu, Wen-Sheng; Su, Shu-Hui; Lin, You-Yen; Chang, Hsin-Hou (Thrombosis and Haemostasis, 2015)
Dengue haemorrhagic fever (DHF) typically occurs during secondary infections with dengue viruses (DENVs). Although it is generally accepted that antibody-dependent enhancement is the primary reason why patients with secondary infection are at an increased risk of developing DHF, a growing body of evidence shows that other mechanisms, such as the elicitation of antiplatelet autoantibodies by DENV nonstructural protein NS1, also play crucial roles in the pathogenesis of DHF. In this study, we developed a “two-hit” model of secondary DENV infection to examine the respective roles of DENV (first hit) and antiplatelet Igs (second hit) on the induction of haemorrhage. Mice were first exposed to DENV and then exposed to antiplatelet or anti-NS1 Igs 24 hours later. The two-hit treatment induced substantial haemorrhage, coagulopathy, and cytokine surge, and additional treatment with antagonists of TNF-α, IL-1, caspase-1, and FcүRIII ameliorated such effects. In addition, knockout mice lacking the Fcү receptor III, Toll-like receptor 3, and inflammasome components Nlrp3 and caspase-1 exhibited considerably fewer pathological alterations than did wild type controls. These findings may provide new perspectives for developing feasible approaches to treat patients with DHF.
Keywords: Autoantibody; dengue virus; Fcे receptor III; Nlrp3 inflammasome; Toll like receptor 3; Shwartzman reaction